The Influence Of Services On Purchase Decisions Of Consumers Minimarket In Tamalate, Makassar City - Nur Hidayah; Haedar Akib; Siti Syarifah Wafiqah Wardah; Syarifuddin (Business Research and Administration Innovation, 2024)
This study examines the effect of minimarket services on consumer purchasing decisions. This study aims to determine how the influence of service on purchasing decisions on minimarket consumers in Tamalate sub-district, Makassar city. This research uses quantitative research methods. Data collection techniques used were observation and questionnaires. The sample used in this study was 100 respondents from the results using the minimarket consumer slovin formula. The data obtained from the research results were processed using data analysis and using descriptive applications and inferential statistical analysis. The results showed that the indicators used in each of these variables indicate where the service is in the good category. For indicators on the purchasing decision variables are in the good category. Based on the results of the T-test analysis through the SPSS.25 program, Tcount is 6206 and Ttable is 1.984, meaning Tcount is greater than Ttable because Tcount > Ttable, then there is a significant influence between services on purchasing decisions. And from the calculation of the determinant coefficient, the R square value is 0.282, which means that the influence of service (X) on purchasing decisions is 28.2 percent, meaning that 28.2 percent of purchasing decisions are influenced by services, while the remaining 71.8 percent is influenced by other factors.